Studies on Thermal Behaviour of Ca-Clinoptilolite Crystals from Marathwada, India - Bhoskar, B.T.; Ghan, S.D. (Asian Journal of Chemistry, 2010)
The freshly extracted zeolite crystals collected from the Marathwada region of India were characterized by X-ray diffraction (XRD), infrared spectroscopy (IR), thermal analyses (TGA/DTA) and wet chemical analysis method as the Ca-clinoptilolite. The powder of the crystals was treated at various temperatures viz., 50, 100, 150,200,250 and 300ºC. At each stage the structural changes were studied by using mid-infrared spectroscopy. Thermogravimetric and differential thermal analysis were used to study the water loss at different stages and the corresponding structural changes. It has been inferred that the structural changes are temperature dependent and can be well studied with the help of infrared spectroscopy.